2019
DOI: 10.1002/jsfa.10021
|View full text |Cite
|
Sign up to set email alerts
|

Short peptides secreted by Bacillus subtilis inhibit the growth of mold on fresh‐cut pumpkin (Cucurbita pepo)

Abstract: BACKGROUND This study investigates the efficacy of short peptides secreted by Bacillus subtilis for fungal inhibition in fresh‐cut pumpkin and for maintaining its shelf life. RESULTS Low‐molecular‐weight filtrate (LC < 1000 Da) of B. subtilis culture (BC) significantly lowered the total number of molds on fresh‐cut pumpkin compared with the untreated control and a BC group after storage. Low‐molecular‐weight filtrate prevented the deterioration of sensory quality in a pumpkin incision, and reduced pectinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The firmness of fresh-cut pumpkins is easily affected by moisture content, lignin formation, and oxidation [27]. Figure 1b shows that the firmness of the four groups of freshcut pumpkins decreased rapidly and then increased slowly.…”
Section: Weight Loss and Firmnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The firmness of fresh-cut pumpkins is easily affected by moisture content, lignin formation, and oxidation [27]. Figure 1b shows that the firmness of the four groups of freshcut pumpkins decreased rapidly and then increased slowly.…”
Section: Weight Loss and Firmnessmentioning
confidence: 99%
“…Similar results were found in fresh-cut carrots [17] and white buttons [28], which indicated that nisin was extremely well maintained in the color of fruit and vegetables. The firmness of fresh-cut pumpkins is easily affected by moisture content, lignin formation, and oxidation [27]. Figure 1b shows that the firmness of the four groups of fresh-cut pumpkins decreased rapidly and then increased slowly.…”
Section: Whitening Index (Wi)mentioning
confidence: 99%
“…His (2-aryl)-Trp-Arg has been reported to antagonize Cryptococcus neoformans ( Sharma et al, 2021 ). In B. subtilis , 57 peptides with less than five amino acids were found to have antifungal activity, among which two tetrapeptides AWYW and HWWY strongly suppressed the growth of Phytophthora capsici and Penicillin chrysogenum ( Qiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%